1992
DOI: 10.1159/000182395
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin Regulation, Oestrogens and the Immune System

Abstract: Several transmitters and neuropeptides participate in the regulation of gonadotropins. At the hypothalamic level, control of gonadotropin releasing hormone (GnRH) involves noradrenaline, GABA, glutamate, angiotensin II, neuropeptide Y, neurotensin, and 5-hydroxytryptamine as well as interleukins 1 and 2. Ovarian steroids can interfere with gonadotropin regulation by either direct effects on GnRH release or by increasing the sensitivity of anterior pituitary cells to GnRH, thus potentiating the release of pitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…This may account for the lack of statistical significance in the decrease in T levels. Experimental studies suggested that IGF-I may stimulate the conversion of testosterone to DHT as addition of IGF-I to cultured genital skin fibroblasts induced a significant increase of 5α-reductase activity possibly resulting in increased DHT in genital skin [35]. However, we did not detect any effect of GH treatment on DHT levels.…”
Section: Discussioncontrasting
confidence: 83%
“…This may account for the lack of statistical significance in the decrease in T levels. Experimental studies suggested that IGF-I may stimulate the conversion of testosterone to DHT as addition of IGF-I to cultured genital skin fibroblasts induced a significant increase of 5α-reductase activity possibly resulting in increased DHT in genital skin [35]. However, we did not detect any effect of GH treatment on DHT levels.…”
Section: Discussioncontrasting
confidence: 83%
“…In 1992, the semiautomatic method CASAS (computer-assisted skeletal age scores) was presented [1] which analyses the 13 bones of the Tanner-Whitehouse (TW) RUS system (RUS stands for radius, ulna and the 11 short bones in rays 1, 3 and 5). CASAS requires a considerable amount of manual work, but yields a smaller interobserver variation than manual rating as well as a smoother longitudinal course of BA over time.…”
Section: Introductionmentioning
confidence: 99%
“…The image of the hand in the form of an X-ray is inserted into the system by the user or radiologist. The preprocessing stage depends on the subsequent stages in the system starting after uploading the radiograph [82]. Usually, the preprocessing step prepares the images for further analysis, for example, removing the background of images or rejecting the images with low quality for processing [83].…”
Section: Discussion and Identified Problemsmentioning
confidence: 99%